Ultrasonic examination of common carotid artery wall elasticity of persons with different stages of internal carotid artery atherosclerosis - Powałowski, T.; Trawiński, Z.; Hilgertner, L. (Archives of Acoustics, 2003)
Ultrasonic methods were used in this study to examine the association between the common carotid artery (CCA) wall elasticity and the atherosclerosis stage in the internal carotid artery (ICA). The degree of stenosis determined ultrasongraphically was used as an indicator of the atherosclerosis stage in the ICA. The examined persons were 45 to 80 years old. They had no arterial hypertension, diabetes mellitus and were not smokers. A comparative study was carried out for cases with ICA atherosclerosis (66 arteries) and without ICA atherosclerosis (61 arteries). In both groups there were persons without and with hypercholesterolemia, which according to our studies had no significant influence on CCA wall elasticity. The CCA wall elasticity was determined by the stiffness coefficient alpha and the distensibility coefficient DC based on ultrasonic measurements. The influences of age and arterial blood pressure on the CCA wall elasticity were taken into account in the analysis. The study revealed a significant decrease of the CCA wall elasticity in the case of patients with atherosclerosis compared with persons without atherosclerosis, and showed a significant correlation between the increase of the ICA stenosis degree and the decrease of CCA wall elasticity.